Efektivitas Pelaksanaan Tugas Satuan Sabhara dalam Menjaga Keamanan dan Ketertiban Masyarakat Kota Medan - Yudhistira Ardana; Syahrul Bakti Harahap (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Medan, as the third largest metropolitan city in Indonesia, faces multidimensional security challenges, evidenced by a 5.8% increase in criminal cases from 2021 to 2023, totaling 8,247 cases in 2023. On the other hand, the condition of Sabhara's facilities and infrastructure at Medan Police shows an average readiness level of only 72.4% of the ideal requirement. This study aims to analyze the effectiveness of the implementation of Sabhara's duties in maintaining security and public order in Medan City. This research uses empirical legal method with a juridical-empirical approach. Data collection was conducted through in-depth interviews, observation, questionnaires, literature study, and documentation. The research location was the Sabhara Unit of Medan Police with 12 informants selected through purposive sampling, consisting of Sabhara leaders and personnel, community leaders, academics, and public lawyers. Data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The results show that the implementation of Sabhara's duties at Medan Police has generally been carried out but has not yet reached optimal effectiveness. The preventive function is implemented through routine patrols and dialogical patrols based on crime mapping in three shifts per day, which has proven to provide a real deterrent effect, as evidenced by the reduction in extortion cases in several areas. The repressive function is implemented by prioritizing persuasive approaches before legal action, although there are notes regarding delayed responses in some riot handling cases. The public service function shows positive development, marked by increased public trust in reporting to the police. Internal factors hindering effectiveness include limited personnel disproportionate to the area and city complexity, limited operational facilities and infrastructure with the largest deficit in radio communication systems and CCTV, and the need for competency improvement in dealing with technology-based crimes. External factors include complex socio-economic dynamics, high population density and heterogeneity, and still weak active community participation in the self-help security system. This study concludes that improving Sabhara's effectiveness requires a multidimensional approach encompassing long-term structural reform, namely fulfilling the ideal personnel ratio, modernizing facilities and infrastructure, and increasing operational budgets, as well as short-term operational management improvements through strengthening community policing, more integrated coordination systems, and transparent and accessible public accountability mechanisms for all levels of society.